A case report on penicillin/co-trimoxazole induced Jarisch Herxheimer reaction in secondary syphilis with human immunodeficiency virus - Narayanan, Suruthi Lakshmi; Ahammed, Afsal; Krishnamurthy, Arun Chander Yadav (International Journal of Basic & Clinical Pharmacology, 2021)
The Jarisch-Herxheimer reaction (JHR) typically occurs after the initiation of antibiotic treatment in syphilis. Although JHR was identified and looked at over many years, the prevention and management of JHR remain unclear. Previous reports have described the occurrence of JHR due to antibiotic treatment in syphilis, we presented a case of a young man with recurrence of JHR in syphilis, first due to penicillin which later was worsened due to co-trimoxazole.